A Terrestrial Gamma‐Ray Flash From the 2022 Hunga Tonga–Hunga Ha'apai Volcanic Eruption - M. S. Briggs; S. Lesage; C. Schultz; B. Mailyan; R. H. Holzworth (Geophysical Research Letters)
Abstract The Hunga Tonga–Hunga Ha'apai submarine volcano recently resumed activity. Violent eruptions on 14th and 15th January 2022 launched a tall ash plume that produced extremely high lightning rates. Here we report a terrestrial gamma‐ray flash (TGF) that was produced by the volcanic lightning and observed from space by the Fermi Gamma‐ray Burst Monitor (GBM). Observations by radio lightning networks and especially by the Geostationary Lightning Mapper show that the only lightning close enough to produce a TGF detectable by Fermi GBM was from the volcano's plume. With the observing duration of Fermi, observing a single TGF is consistent with the hypothesis that the volcanic lightning of this eruption produced TGFs at the average rate of thunderstorm lightning. The observation of a strong TGF from space also indicates that the electric field was oriented so as to accelerate electrons upward.